The social representation of sportswomen in Tunisia - Khalifa, R.; During, B.; Feki, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Since its independence (1956), Tunisia is the only Arabic country where women and men enjoy equal rights. This presents a dilemma between modernity and tradition. Women are equal to men in several domains, but when it comes to sports, where the women`s body is directly implicated, the situation is no longer equal. Methods The purpose of the present investigation is to study the social representation of sportswomen. The study aims to compare self image as it is perceived by two groups of third and fourth-year students from Tunisian universities. The subjects included 200 students in Sciences and Techniques of Sports and Physical Activities and 200 students from the Literature faculty. Results / Discussion The results demonstrated that the representations of the two populations are still traditional and filled with Arabic Muslim values based on sex separation. Dance and Gymnastics are the only sports considered as very feminine and graceful. The other sports are rather masculine. Fighting sports, weightlifting, rugby, and football, remain the conservatories of virility. Women can become more masculine by participating in these sports. On the one hand, the researchers could see new legitimacy for females exercising in sports. On the other hand, the authors observed a permanency of the sexual division which is limiting female participation in all sports without discrimination. While women are starting to practice sports that were restricted to men, they are still not encouraged sufficiently to continue their sports career.